Protein Metabolism and Homeostasis in Aging - Tavernarakis, Nektarios. (Advances in Experimental Medicine and Biology, 2010)
The focus of this book is on the role of protein metabolism and homeostasis in aging. An overview is provided of the current knowledge in the area, including protein synthesis, accuracy and repair, posttranslational modifications, degradation and turnover, and how they define and influence aging. The chapters mainly focus on wellcharacterized factors and pathways, but new areas are also presented, where associations with aging are just being elucidated by current experimental data.